The Lucerne Toolbox 2 to optimise axillary management for early breast cancer: a multidisciplinary expert consensus - Kaidar-Person, Orit; Pfob, André; Gentilini, Oreste Davide; Borisch, Bettina; Bosch, Ana; Cardoso, Maria João; Curigliano, Giuseppe; De Boniface, Jana; Denkert, Carsten; Hauser, Nik; Heil, Jörg; Knauer, Michael; et al. (EClinicalMedicine, 2023)
Clinical axillary lymph node management in early breast cancer has evolved from being merely an aspect of surgical management and now includes the entire multidisciplinary team. The second edition of the “Lucerne Toolbox”, a multidisciplinary consortium of European cancer societies and patient representatives, addresses the challenges of clinical axillary lymph node management, from diagnosis to local therapy of the axilla. Five working packages were developed, following the patients’ journey and addressing specific clinical scenarios. Panellists voted on 72 statements, reaching consensus (agreement of 75% or more) in 52.8%, majority (51%-74% agreement) in 43.1%, and no decision in 4.2%. Based on the votes, targeted imaging and standardized pathology of lymph nodes should be a prerequisite to planning local and systemic therapy, axillary lymph node dissection can be replaced by sentinel lymph node biopsy ( ± targeted approaches) in a majority of scenarios; and positive patient outcomes should be driven by both low recurrence risks and low rates of lymphoedema.